Culturally Responsive Leadership In Education: Integrating Maja Labo Dahu For School Quality Improvement - Suratman, Suratman; Arifin, Imron; Burhanuddin, Burhanuddin; Sobri, Ahmad Yusuf (Journal of Neonatal Surgery, 2025)
The study examines the integration of Maja Labo Dahu, a leadership philosophy rooted in Bima’s local wisdom, into school management at SMA Negeri 1 Kota Bima to address challenges related to educational quality, student performance, and cultural integration. This research aims to analyze the core values of Maja Labo Dahu, evaluate their impact on school leadership and student outcomes, and propose a culturally responsive leadership framework. Using a qualitative case study approach, data were collected through semi-structured interviews, participant observations, and document analysis, followed by an inductive thematic analysis. The findings indicate that the application of Maja Labo Dahu values—collective decision-making, prioritizing the common good, and mutual respect—significantly improves school governance, teacher performance, student engagement, and overall educational outcomes. The research highlights the role of culturally embedded leadership in fostering inclusivity, strengthening school-community relationships, and enhancing learning environments. This study contributes to the discourse on culturally responsive educational leadership by demonstrating how indigenous leadership philosophies can be systematically integrated into modern school management. The results offer practical implications for educational policymakers and school leaders in Indonesia, emphasizing the necessity of culturally informed leadership training and policy frameworks. Future research should explore the long-term effects of Maja Labo Dahu leadership on school performance and expand its application to different educational settings to assess its broader impact on educational quality and cultural preservation.